# 18×(7+(-3))=(18×7)+(18×(-3))

2
by gub

2015-10-02T17:32:08+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

18 x (7-3)= (18 x 7 ) + (18 x (-3)

72 = 126 + (-54)

72 = 72

oh well....
hi
umm hey
2015-10-02T18:48:17+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
18×(7+(-3)) = 18×(7 - 3) = 18×(4) = 72
(18×7)+(18×(-3)) = 126 + (-54) = 126 - 54 = 72

Hence 18×(7+(-3))=(18×7)+(18×(-3))
It is called the distributive property.
hi
wwlcome
Hiii
When you want to talk to someone, use message or comment on their profiles.
ok